Penggunaan Podcast sebagai Alat Komunikasi Pemasaran Studi Kasus Penerimaan Mahasiswa Baru Universitas Pamulang - Fauzi, Rini Dianti; Anggraini, Katry; Sewaka, Sewaka (Sekolah Menengah Kejuruan (SMK) Pustek, 2025)
Podcasts as a digital audio medium have experienced rapid growth in recent years. Its flexible and accessible format makes it an effective tool for conveying information and building relationships with audiences. Marketing communication is a means used in an effort to inform, persuade and remind consumers either directly or indirectly about the products and brands they sell. Marketing communication is a means used in an effort to inform, persuade and remind consumers either directly or indirectly about the products and brands they sell. The purpose of this research is to determine the use of podcasts as a marketing communication tool: Case Study of Pamulang University New Student Admissions. This research uses interpretative qualitative research methods. There are several techniques that can be used for the data collection process. In this research, the data collection techniques used were observation, documentation, literature study. The research results show that Podcasts have become an effective medium in Pamulang University's marketing communications strategy. Through podcasts, universities can convey various important and interesting information to prospective students in a more personal and easily accessible way. In addition, podcasts provide flexibility for prospective students to listen to information anytime and anywhere. The audio format presented in podcasts allows listeners to absorb information more comfortably compared to reading brochures or viewing promotional videos. Podcasts can create a stronger emotional connection with prospective students.